PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU YANG MENYEBARKAN STIKER YANG BERMUATAN PORNOGRAFI MELALUI APLIKASI PESAN INSTAN WHATSAPP MENURUT UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Frengki Sanjaya; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Cyber porn is a crime that is rife. One of the media for spreading pornographiccontent is through the form of instant message stickers containing pornography in theWhatsApp instant messaging application which is distributed by its users. As a crime,perpetrators who distribute pornographic stickers can be held criminally responsiblebased on existing laws. Therefore, writing this thesis formulates two problemformulations namely; first, how is the legal arrangement related to pornography inIndonesia. Second, what is the criminal responsibility for the perpetrators who distributestickers containing pornography based on Law Number 19 of 2016 concerningAmendments to Law Number 11 of 2008 concerning Information and ElectronicTransactions.This research is classified in the type of normative legal research. The researchwas carried out by examining secondary data as well as an approach to laws. Thisresearch examines the legal principles contained in Law Number 19 of 2016 concerningAmendments to Law Number 11 of 2008 concerning Information and ElectronicTransactions and statutory regulations. -other related invitations. The data sources usedare primary data, secondary data and tertiary data. The data collection technique in thisstudy was by means of interviews and literature review and this research is normativejuridical in nature. After the data has been collected, it is then analyzed qualitatively,then draws conclusions using a deductive thinking method, namely analyzing problemsfrom a general form to a special form.This research explains that the regulation of pornography law in Indonesia is quiteclear as positive law, as stipulated in the Criminal Code, Law No. 44 of 2008 concerningPornography, Law Number 19 of 2016 concerning Amendments to the Law Number 11 of2008 concerning Information and Electronic Transactions and Law no. 1 of 2023concerning the Criminal Code. The act of distributing stickers containing pornographybased on Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008concerning Information and Electronic Transactions can be held criminally liable withthe concept of criminal liability.Keywords: Pornography - Criminal Actions - Criminal Liability